Mối quan hệ giữa nguồn kiến thức và sự đổi mới của nhân viên: Vai trò của kỹ năng vận hành và tính cách chủ động - Lê Công, Thuận; Phạm Tô Thục , Hân; Bùi Thị , Thanh; Phan Quốc, Tấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
Although knowledge plays a vital role in motivating employee innovation, a paucity of research has investigated the effect of knowledge sourcing on employee innovation through mediators and moderators. Drawing on the Ability – Motivation – Opportunity (AMO) model, this paper investigates the effects of knowledge sourcing, operational skills, and proactive personality on employee innovation. This study used confirmatory factor analysis and structural equation modeling to analyze the data. The results showed that knowledge sourcing had a positive effect on employee innovation. Moreover, operational skills mediated this relationship. Furthermore, proactive personality positively moderated the impact of knowledge sourcing on employee innovation. Therefore, this paper has some theoretical contributions and managerial implications in stimulating employee innovation.
Keywords: Proactive personality; Employee innovation; Knowledge sourcing; Operational skills